Albinismo en Carancho (Caracara plancus) y Gaviota Cocinera (Larus dominicanus) - Petracci, Pablo F.; Delhey, J. Kaspar V.; Pérez, Cristian H. F. (Nuestras Aves, 2001)
Este artículo no cuenta con un resumen.